Historia de España Alfaguara / dirigida por Miguel Artola. Vol. 2. La época medieval / José Angel García de Cortázar - Artola, Miguel (1923-) García de Cortázar y Ruiz de Aguirre, José Angel (Alianza Universidad ; 40)
3° ed. de 1976, 8° ed. de 1981, 9° ed. de 1983 | Bibliografía. Índices